2009
DOI: 10.1111/j.1399-5618.2008.00642.x
|View full text |Cite
|
Sign up to set email alerts
|

Eyeblink conditioning anomalies in bipolar disorder suggest cerebellar dysfunction

Abstract: Despite the extraordinary personal and societal burden of bipolar disorder (BD), relatively little is known about neural mechanisms associated with the unusual swings and shifts in affective and cognitive function that characterize the disorder. Accumulating evidence suggests that structures (e.g., the cerebellum and basal ganglia) and neurotransmitter systems (e.g., dopamine and glutamate) associated with neural timing processes are abnormal in mood disorders (1-5). The overarching theoretical model under inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 70 publications
(127 reference statements)
10
29
0
Order By: Relevance
“…Moreover, lesions to the cerebellum can cause disturbances in mood including mania, depression, and mood lability [65]. Finally, our group has documented abnormalities in bipolar disorder on several tasks for which the cerebellum is critical including classical delay eyeblink conditioning [66], paced finger tapping [28], and postural sway [67]. This evidence supports a possible role for the cerebellum in bipolar disorder and suggests that dysfunctional cerebellar circuitry may contribute to timing deficits observed in the present study.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, lesions to the cerebellum can cause disturbances in mood including mania, depression, and mood lability [65]. Finally, our group has documented abnormalities in bipolar disorder on several tasks for which the cerebellum is critical including classical delay eyeblink conditioning [66], paced finger tapping [28], and postural sway [67]. This evidence supports a possible role for the cerebellum in bipolar disorder and suggests that dysfunctional cerebellar circuitry may contribute to timing deficits observed in the present study.…”
Section: Discussionsupporting
confidence: 84%
“…The cerebellum is a brain area that has long been considered to be mainly important for the control of movement [32,33] . However, the cerebellum has also been associated with attention [34] , working memory [35] , language [36] , executive functions [37] , emotion and affection [38][39][40] . The cerebellum can be divided into three parts: the anterior lobe (lobuli I-V), the posterior lobe (lobuli VI-IX) and the medial flocculonodular lobe (lobule X) [41] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research using a single-cue delay EBC paradigm found deficits in clinical groups with conditions including schizophrenia Brown et al, 2005), bipolar disorder (Bolbecker, Mehta, Johannesen, et al, 2009), and drug abuse (Skosnik et al, 2007). However, few studies involving the CS-US ISI have been completed, and none involving clinical groups.…”
Section: Discussionmentioning
confidence: 99%